Multimedia Interaktif BUDLI (Body Literasi) : Multimedia Interaktif Pada Mata Pelajaran Bahasa Inggris Untuk Meningkatkan Literasi Digital Siswa kelas V Sekolah Dasar - Ni Made Dwitayani; I Gde Wawan Sudatha; I Made Tegeh (Jurnal Media dan Teknologi Pendidikan, 2025)
Preliminary observations revealed low levels of digital literacy and student learning outcomes in English subjects. This condition necessitates the development of instructional media that responds to the demands of 21st-century learning. This study aims to design and develop the BUDLI interactive multimedia, validate its quality through expert assessments and limited trials, and evaluate its effectiveness in enhancing digital literacy and English learning outcomes of fifth-grade elementary school students. This research is a development study employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 30 fifth-grade students. Data were collected through questionnaires and tests, and analyzed using qualitative descriptive, quantitative descriptive, and inferential statistical methods (t-test). The findings show that: (1) the development process of BUDLI interactive multimedia followed the ADDIE stages systematically; (2) the multimedia was deemed valid based on assessments by content experts (96%), design experts (93%), media experts (95%), individual trials (92%), and small group trials (79.32%); and (3) BUDLI interactive multimedia was proven effective in improving digital literacy and learning outcomes, as indicated by the t-test significance value of 0.0001 < 0.05. It is concluded that BUDLI interactive multimedia is effective as a learning tool to support the enhancement of digital literacy and English learning outcomes in elementary education.